Acquiring Counseling Skills in Mid-Career: Outcomes of a Distance Education Course for Practicing Audiologists - English, Kris; Rojeski, Tom; Branham, Kerri (Journal of the American Academy of Audiology, 2000)
Although considered an essential component of audiology service delivery, counseling skills often are not adequately addressed in graduate training programs. One of the many goals of the audiology doctorate is to address this deficit by providing formal course work in counseling for both traditional graduate students and practitioners. This study describes the outcomes of a counseling class taught via distance education to mid-career audiologists, who initially were found to provide informational or technical responses to affective patient comments (a so-called "communication mismatch"). In spite of inherent limitations in electronic instruction, students demonstrated learning outcomes comparable to those obtained from conventional classroom instruction, including an improvement in their ability to respond to the affective nature of patient comments.
Keywords: Counseling; distance education